A review on major business excellence frameworks. - Dodangeh, Javad; Mohd Yusuff, Rosnah; Ismail, Napsiah; Ismail, Md. Yusof; Beik Zadeh, Mohammad Reza; Jassbi, Javad (2013)
In increasingly competitive business environments, business excellence models play crucial roles in organizational successes. Numerous organizations implement business excellence models to obtain business excellence. To monitor the progress towards business excellence, thousands of organizations across the world use business excellence frameworks. This paper reviews the principal concepts of excellence and the leading quality awards, including the Deming Prize from Japan, the Malcolm Baldrige National Quality Award (MBNQ) from the United States, the European Foundation for Quality Management (EFQM) excellence model and The ISO 9000 quality system and describes how they may be applied to direct organizational improvement by means of the process of self-assessment. Ultimately, these business excellence frameworks were evaluated against a set of 12 sub-systems which they constructed to include all aspects of the Total Quality Management philosophy. The results of this evaluation have been discussed as a summary of comparison between major business excellence frameworks.